Youth vaping prevention with urban Indigenous communities of the southwest U.S.: a protocol for a randomized controlled trial - Ayers, Stephanie L.; Ignacio, Matt; Begay-Kroupa, Jolyana; Oesterle, Sabrina; Okamoto, Scott K.; Reep, Zoe K.; June, Danielle; Kulis, Stephen S. (Frontiers in Public Health, 2025)
BackgroundIndigenous adolescents have the highest rates of nicotine vaping and tend to initiate at an earlier age compared to other racial and ethnic groups. Despite this, no evidence-based intervention currently exists to prevent nicotine and cannabis vaping for Indigenous youth.MethodsThis study will partner with a long-established community organization and an Indigenous Youth Advisory Board to better understand the key risk and protective factors associated with vaping among urban American Indian youth of the Southwest U.S. The study will also adapt and test through a randomized controlled trial Living in 2 Worlds, an empirically supported substance use prevention intervention, to specifically target nicotine and cannabis vaping in urban American Indian youth. The Indigenous Youth Advisory Board will be actively involved throughout the research process, helping to guide the study, ensure meaningful youth participation, and changes in their confidence, leadership, and collaboration will be assessed.DiscussionThis study builds on the strengths of the urban Indigenous community and long-standing partnerships to address a critical need: reducing vaping disparities among Indigenous youth and their associated health impacts. By developing an evidence-based, culturally relevant, and sustainable intervention, this research aims to create lasting change and help eliminate racial and ethnic disparities in substance use.